DEA efficiency of Serbian banks - comparison of three approaches - Marcikić Horvat, Aleksandra; Milenković, Nada; Radovanov, Boris; Zelenović, Vera; Milić, Dragana (Anali Ekonomskog fakulteta u Subotici, 2023)
The aim of this paper is to analyze three approaches in order to give a comprehensive analysis of the efficiency of the banking sector in Serbia. The paper analyses the intermediate, operating and profitability approach for measuring bank efficiency. The paper applies a non-parametric data envelopment analysis (DEA) on a sample of 23 banks operating in Serbia in the period during and after the covid-19 pandemic, ie. for 2019, 2020 and 2021. The results of the analysis showed that the highest efficiency is according to the intermediate approach, while the lowest efficiency of banks is in the approach of measuring profit efficiency. To the results of the analysis should be added the fact that the lowest levels of efficiencies in each approach were achieved by small banks with a small market share. The results of the research are certainly influenced by low interest rates and the activities of mergers and acquisitions, which are intensive on the Serbian banking market.